2021
DOI: 10.1007/s12031-021-01942-3
|View full text |Cite
|
Sign up to set email alerts
|

Identification of ITPR1 as a Hub Gene of Group 3 Medulloblastoma and Coregulated Genes with Potential Prognostic Values

Abstract: The Group 3 Medulloblastoma ( Grp3-MB ) is an aggressive molecular subtype with a high incidence of metastasis and deaths. In this study, were used an RNA sequencing data ( RNA-Seq ) from a Brazinian cohort of MBs to identify hub genes associated with the metastatic risk. Data validation were performed by using multiple large datasets from MBs (GSE85217, GSE37418, EGAS00001001953). DESeq2 package in R software was used to identify the differentially expressed genes ( DEGs ) in our RNA-Seq data. The DEGs data w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…A high level of KIRREL2 expression was also associated with unfavorable survival for all second-generation subgroups from II to VII (not shown). However, we did not find any clinical significance for genes which were previously reported as molecular Grp 3 MB prognosticators [ 2 , 8 , 9 , 18 , 19 , 24 , 27 , 33 ] but were not included in the current DEG set (Online Resource Supplementary Table 2).
Fig.
…”
Section: Resultsmentioning
confidence: 62%
See 1 more Smart Citation
“…A high level of KIRREL2 expression was also associated with unfavorable survival for all second-generation subgroups from II to VII (not shown). However, we did not find any clinical significance for genes which were previously reported as molecular Grp 3 MB prognosticators [ 2 , 8 , 9 , 18 , 19 , 24 , 27 , 33 ] but were not included in the current DEG set (Online Resource Supplementary Table 2).
Fig.
…”
Section: Resultsmentioning
confidence: 62%
“…Therefore, a more refined understanding of Grp 3 MB molecular heterogeneity is urgently needed for improved risk stratification, optimization of current treatments, and the development of subgroup-directed therapies. Studies investigating the clinical significance of various molecular features in Grp 3 MB at higher genomic resolution have recently been reported, identifying a wide range of prognostically relevant molecular patterns and subtypes [ 2 , 3 , 8 , 9 , 11 , 15 , 18 21 , 24 , 27 30 ]. Thus, combined multiple class-definition approaches to DNA-methylation profiles of Grp 3/Grp 4 MB identified eight second-generation subgroups, labeled I–VIII [ 21 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…RALGPS1 and RALGPS2 contain pleckstrin homology domains but their means of regulation are not well understood [47]. In cancer, elevated expression of numerous RALGEFs is associated with poor survival and increased local invasion and distant metastasis [48][49][50][51][52]. Downregulation of several RALGEFs has been shown to decrease the invasion and migration of cancer cells both in vitro and in vivo through decreased RALA or RALB activity [49,[52][53][54][55][56][57][58].…”
Section: Regulation Of Ral Activationmentioning
confidence: 99%
“…For example, the lower expression of ITRR1 and its coregulated genes ( ATP1A2, MTTL7A, RGL1 ) are associated with processes in MB, and the lower expression of ANTXR1 and RGL1 are significantly correlated with worse overall survival (OS). [ 10 ] However, until now fewer clinical studies have identified novel genes directly against metastasis of MB. Accordingly, further investigation of metastasis related genes is helpful to better understand the molecular mechanisms of the occurrence of MB metastasis and provide more options for clinical treatment.…”
Section: Introductionmentioning
confidence: 99%